The first photometric analysis and period investigation of the K-type W UMa type binary system V0842 Cep - Li, Yu-Yang; Li, Kai; Liu, Yuan (Research in astronomy and astrophysics, 2021)
V0842 Cep is a W UMa-type binary star that has been neglected since its discovery. We analysed the VR c I c light curves, obtained by the 1 m telescope at Weihai Observatory of Shandong University, using the Wilson-Devinney code. V0842 Cep was found to be a shallow contact binary system ( f = 8.7%) with a mass ratio of 2.281. Because its orbital inclination is greater than 80°, the photometric results are reliable. A period study is included which reveals a continually decreasing orbital period ( d p d t = 1.50(±0.42)×10 −7 d yr −1 ). This trend could be attributed to the angular momentum loss via stellar wind.